1998
DOI: 10.4039/ent130869-6
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF A NEEM (AZIDIRACHTA INDICA) BASED INSECTICIDE ON SURVIVAL AND DEVELOPMENT OF JUVENILE WESTERN CHERRY FRUIT FLY (RHAGOLETIS INDIFFERENS) (DIPTERA: TEPHRITIDAE)

Abstract: The Canadian Entomologist 130: 859 -867 (1998) Effects of photoperiod, time of year, temperature, and an insect growth regulator (fenoxycarb) on ovarian development rate in overwintering pear psylla, Cacopsylla pyricola (Foerster), were determined. Winterform pear psylla were collected from the field at intervals between October and February, and reared at 20°C and one of three treatments: short-day photoperiod, long-day photoperiod, or short-day Xhfl THE CANADIAN ENTOMOLOGIST November/December 1998 Ct C st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The extracts inhibited the number of hatching eggs and/or turned eggs and larvae unviable after oviposition for at least 72 hr, effects that were also described by Van-Randen and Roitberg (1998b) . The high percentage of larviform pupae in the treatments ( Table 3 ), especially in insects that fed on the ethyl acetate fruit extract treatment, indicates that the triterpenoids and limonoids interfered with the hardening of the cuticle and the stabilization of protein structures ( Cruz 2000 ).…”
Section: Discussionmentioning
confidence: 59%
“…The extracts inhibited the number of hatching eggs and/or turned eggs and larvae unviable after oviposition for at least 72 hr, effects that were also described by Van-Randen and Roitberg (1998b) . The high percentage of larviform pupae in the treatments ( Table 3 ), especially in insects that fed on the ethyl acetate fruit extract treatment, indicates that the triterpenoids and limonoids interfered with the hardening of the cuticle and the stabilization of protein structures ( Cruz 2000 ).…”
Section: Discussionmentioning
confidence: 59%
“…neem extracts (Chen et al 1996;Masood et al 2009;Ali et al 2011). The extracts inhibited the number of hatching eggs and/or turned eggs and larvae unviable after oviposition for at least 72 hr, effects that were also described by Van-Randen and Roitberg (1998b). The high percentage of larviform pupae in the treatments (Table 3), especially in insects that fed on the ethyl acetate fruit extract treatment, indicates that the triterpenoids and limonoids interfered with the hardening of the cuticle and the stabilization of protein structures (Cruz 2000).…”
Section: Discussionmentioning
confidence: 75%
“…The studies of Shivendra & Singh (1998), Shakunthala & Thomas (2001a) and Tewari (2001) revealed the insecticidal properties of A. calamus and A. indica against fruit flies. Assessing the efficacy of neem extracts by applying them along with food, Van Randen & Roitberg (1998) reported an inverse effect on adult survival and on the development of eggs of Western fruit fly. Van Randen & Roitberg (1998) also reported that the artificial diet containing neem based insecticides has negative effect on pupae formation and adult emergence of Western fruit fly.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the efficacy of neem extracts by applying them along with food, Van Randen & Roitberg (1998) reported an inverse effect on adult survival and on the development of eggs of Western fruit fly. Van Randen & Roitberg (1998) also reported that the artificial diet containing neem based insecticides has negative effect on pupae formation and adult emergence of Western fruit fly. Shakunthala & Thomas (2001b) indicated the significant changes in the appearance of reproductive organs of adult B. cucurbitae when the flies were fed with a diet containing A. calamus extract.…”
Section: Discussionmentioning
confidence: 99%